Selection of Environmentally Friendly Material Alternatives to Replace Single-Use Plastics in Cafes and Restaurants Using Multicriteria Analysis Methods: A Case Study of Banda Aceh - Muhammad Haikal; Muhammad Aslam Alkindy; Cut Nurul Syifa Aiyub; Muhammad Al-Aqsal; Siti Irhamna (Journal of Innovative and Creativity (Joecy), 2026)
Single-use plastics are widely used in food-service businesses because they are inexpensive, lightweight, and convenient, but their short service life intensifies persistent waste generation. This study ranked material alternatives for cafes and restaurants by integrating business-owner and consumer preferences. A cross-sectional survey was conducted in Banda Aceh from January to June 2025. Twenty-four establishments (12 cafes and 12 restaurants) were selected from 568 registered businesses, yielding 24 owner or manager responses and 24 consumer responses. Ceramic, stainless steel, glass, reusable plastic, and bioplastic were evaluated using nine environmental, economic, and social criteria and the Simple Additive Weighting method. Owners ranked bioplastic highest (20.45), whereas consumers preferred ceramic (18.41). In the combined assessment, ceramic ranked first at 36.55 (20.81%), followed closely by bioplastic at 35.99 (20.49%) and glass at 35.91 (20.45%). Low carbon footprint was the most influential combined criterion (13.77%). The narrow differences show that no material is universally superior: ceramic is balanced for dine-in service, while glass and verified bioplastic provide complementary options for beverage and takeaway applications.